GE_GERICHTE P/10038/2011 vom 23. Februar 2017 - GE Cour de justice (2017)
IN DUBIO PRO REO ; ABUS DE CONFIANCE ; CONTRAT FIDUCIAIRE ; BANQUE ; SOCIÉTÉ DE DOMICILE ; DÉPENS | CP.138.1.2; CPP.126; CPP.428; CPP.429; CPP.433